Numerical analysis of MHD natural convection in a partially open cavity with internal energy source. (2018) - Nithyadevi, N.; Rajarathinam, M.
In this paper, the problem of MHD natural convection in a partially open square cavity in the presence of internal energy source has been studied numerically. The bottom and vertical walls are isothermally heated and cooled by different constant temperatures. The top wall of the cavity has been opened in three different positions namely, left, middle and right whereas the remaining unopened part is thermally insulated. The governing nonlinear partial differential equations are solved by SIMPLE algorithm where the discretitation is followed by finite volume method. The influence of various pertinent parameters such as internal Rayleigh number, external Rayleigh number and Hartmann number are discussed via graphs and tables. It is found that the fluid flow and heat transfer are strongly depends on the internal and external Rayleigh numbers, Hartmann number and three different opening positions of the top wall.